Cybercrime en Masse in the Digital India: A Case Study - Dr. Siddhant Chandra, (Indian Journal of Mass Communication and Journalism (IJMCJ), 2025)
Cyberspace is essentially a digital universe where people establish their online identities, and it has been expanding rapidly in recent years, mainly due to the widespread adoption of the internet and the rise of smartphones. What began as basic online activities, such as emailing and web surfing, has now grown to influence nearly every aspect of our daily lives, including how we communicate, bank, travel, and shop. The increase in smartphone usage has made the internet more accessible, leading to greater independence, new economic opportunities, and societal shifts. Government programs, such as the Jan Dhan Yojana, and the emergence of digital payment systems following demonetization have further advanced India’s journey toward a digital economy. However, this digital shift also brings with it a heightened risk of cybercrimes, especially since many users aren’t well-versed in technology. States such as Karnataka and Jharkhand have reported an increase in cyber offences, underscoring the pressing need for enhanced cybersecurity measures and improved digital literacy. This paper examines the growth of cyberspace, its societal implications, and the challenges we face in ensuring secure digital participation.